1994
DOI: 10.4012/dmj.13.240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapid Burnout Type Gypsum-bonded Investment on Performance of Castings

Abstract: Rapid burnout type gypsum-bonded investment materials were developed to shorten the time required for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Blackman (2000) [7] measured marginal sharpness and diameter changes for crowns cast with type III gold alloy by using phosphate-bonded investment and rapid burnout techniques, and concluded that rapid mould preparation resulted in loss of marginal fineness. Murakami et al (1994) [8] studied the rapid burnout technique with gypsum-bonded investment to examine surface aspects and fit of complete crowns and noted that, less expansion had occurred and was probably responsible for increased gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Blackman (2000) [7] measured marginal sharpness and diameter changes for crowns cast with type III gold alloy by using phosphate-bonded investment and rapid burnout techniques, and concluded that rapid mould preparation resulted in loss of marginal fineness. Murakami et al (1994) [8] studied the rapid burnout technique with gypsum-bonded investment to examine surface aspects and fit of complete crowns and noted that, less expansion had occurred and was probably responsible for increased gaps.…”
Section: Discussionmentioning
confidence: 99%
“…In the accelerated method, the mold is introduced in a preheated furnace (set at maximum recommended temperature) as soon as it achieves adequate wet strength (12 to 15 minutes) . This eliminates the wax pattern rapidly within 12 to 15 minutes …”
mentioning
confidence: 99%
“…9 Accelerated/rapid wax-elimination methods have been reported to reduce laboratory time and achieve similar casting accuracy in 30 to 40 minutes. [10][11][12][13][14][15] In the accelerated method, the mold is introduced in a preheated furnace (set at maximum recommended temperature) as soon as it achieves adequate wet strength (12 to 15 minutes). [11][12][13][14] This eliminates the wax pattern rapidly within 12 to 15 minutes.…”
mentioning
confidence: 99%
See 2 more Smart Citations